Sosialisasi Pelaksanaan Assembling dalam Meminimalisir Ketidaklengkapan Pengisian Rekam Medis di RS Awal Bros Botania Batam - Ernaman Putri, Riza Suci; Putri, Widya; Wahyudi, Wahyudi (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2025)
Hospitals play a crucial role in improving public health, therefore hospitals are expected to uphold efficient medical recording practices. The completeness of medical records is vital as it directly impacts the health services provided by medical staff and the overall quality of the hospital's services. When doctors thoroughly fill out medical records, it makes it easier for health workers in the records department to organize data and generate useful information for hospital management. Inadequate communication between doctors and nurses often leads to incomplete medical records. Effective communication between these healthcare professionals within the records department is crucial as it directly affects patient care quality and safety. Negligence by staff also contributes to incomplete medical records, potentially compromising patient care. Medical record officers should consistently educate healthcare providers on the importance of complete medical records, emphasizing the benefits and objectives of maintaining thorough records to ensure high-quality hospital services.